Human stimulus reliability during an offensive and defensive agility protocol - Spiteri, T.; Cochrane, J. L.; Nimphius, S. (Journal of Australian Strength and Conditioning, 2012)
Athletes are required to change direction in response to opposition movements during offensive and defensive orientations throughout the duration of a game. Currently, humans have been used as a stimulus during agility protocols performing movements for athletes to respond to. However, the reliability of these movements and running times during offensive and defensive conditions has yet to be examined. Therefore, the purpose of this study was to assess the reliability of athlete running times and movements performed by a human stimulus. One human stimulus was tested across two sessions completing 200 movement patterns, with five athletes performing agility trials responding to the human stimulus during offensive and defensive conditions. All variables analysed display moderate to substantial intraday reliability, revealing movements performed by the human stimulus (intraclass correlation coefficient (ICC): 0.71-0.99; coefficient of variation (CV): 1.11-4.77; typical error (TE): 0.15-0.59) and athlete running times (offensive: ICC: 0.91; CV: 3.30; TE: 0.06, defensive: ICC: 0.90; CV: 3.60; TE: 0.05) to be reliable. Further, no significant difference (p>/=0.05) was observed for human stimulus movement variables or athlete running times between the two testing sessions, however athletes produced a significantly faster running time (p = 0.009) during the defensive condition. Results suggest the movements performed by a human stimulus can be reliable supporting the implementation of a human stimulus during agility protocols to detect the smallest worthwhile change in athletic performance. Further, the results indicate the importance of measuring athlete`s agility performance during both offensive and defensive conditions as a guide for training programs to improve agility performance.